Healthcare worker and family caregiver hand hygiene in Bangladeshi healthcare facilities: results from the Bangladesh National Hygiene Baseline Survey. Issue 3 (November 2016) - Horng, L.M.; Unicomb, L.; Alam, M.-U.; Halder, A.K.; Shoab, A.K.; Ghosh, P.K.; Opel, A.; Islam, M.K.; Luby, S.P.
Summary: Background: Healthcare facility hand hygiene impacts patient care, healthcare worker safety, and infection control, but low-income countries have few data to guide interventions. Aim: To conduct a nationally representative survey of hand hygiene infrastructure and behaviour in Bangladeshi healthcare facilities to establish baseline data to aid policy. Methods: The 2013 Bangladesh National Hygiene Baseline Survey examined water, sanitation, and hand hygiene across households, schools, restaurants and food vendors, traditional birth attendants, and healthcare facilities. We used probability proportional to size sampling to select 100 rural and urban population clusters, and then surveyed hand hygiene infrastructure in 875 inpatient healthcare facilities, observing behaviour in 100 facilities. Findings: More than 96% of facilities had 'improved' water sources, but environmental contamination occurred frequently around water sources. Soap was available at 78–92% of handwashing locations for doctors and nurses, but just 4–30% for patients and family. Only 2% of 4676 hand hygiene opportunities resulted in recommended actions: using alcohol sanitizer or washing both hands with soap, then drying by air or clean cloth. Healthcare workers performed recommended hand hygiene in 9% of 919 opportunities: more after patient contact (26%) than before (11%). Family caregivers frequently washed hands with only water (48% of 2751 opportunities), but with little soap (3%). Conclusion: Healthcare workers had more access to hand hygiene materials and performed better hand hygiene than family, but still had low adherence. Increasing hand hygiene materials and behaviour could improve infection control in Bangladeshi healthcare facilities.